2019
DOI: 10.3991/ijet.v14i22.11747
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Electronic Device to Teach English as a Foreign Language: Educational Toy for Pre-Kindergarten Children

Abstract: This Educational toys are important in early child development and motivate children to learn language. Numerous digital toys are now available in the children’s educational toys market to help children learn foreign languages. However, a number of such technologies are expensive and the quality of usability is not at an acceptable level. The aim of the study is to develop a cost-effective, sustainable and danger-free educational toy for pre-kindergarten children aged between 4-5 years old to teach English as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…A series of comparative studies by Wen Qi fang were conducted on the critical thinking ability between college students majoring in foreign languages and other college students majoring in art and science [5][6]. Some scholars studied the reasons for the lack of critical thinking ability of current college students and the training program, and involved the cultivating the critical thinking ability of foreign language teachers in colleges and universities [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A series of comparative studies by Wen Qi fang were conducted on the critical thinking ability between college students majoring in foreign languages and other college students majoring in art and science [5][6]. Some scholars studied the reasons for the lack of critical thinking ability of current college students and the training program, and involved the cultivating the critical thinking ability of foreign language teachers in colleges and universities [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Hişmanoğlu et al (2017) such as qualitative research methodology, while Gangaiamaran & Pasupathi (2017) used a systematic literature review. Quantitative and qualitative methods were identified in two research articles (Abdi & Cavus, 2019;Rezaei et al, 2014). However, several studies did not identify the research design used Jin, 2017;Kukulska-Hulme, Norris, & Donohue, 2017)…”
Section: Methodsmentioning
confidence: 99%
“…Some studies showed that both students and teachers preferred mobile applications to teach and learn English (Mirzaei et al, 2018). Mobile-assisted teaching helps learner improve their vocabulary and increase confidence in participating in the classroom (Rezaei et al, 2014), and they make learning enjoyable (Abdi & Cavus, 2019;Gangaiamaran & Pasupathi, 2017). However, some research showed that weak learners are reluctant to use mobile apps to learn English (Wu, 2019).…”
Section: Context Of Usagementioning
confidence: 99%
“…To test the research reliability (i.e., the consistency of the research measure), the Cronbach's Alpha value of ≤ 0.60 is regarded not reliable, whereas that of ≥ 0.70 is considered totally acceptable. The reliability test for this research study is summarized and shown in Tables (1) and (2). Seeking the external validity and representativeness, the researcher randomly selected the participants.…”
Section: Instrument Reliability and Validitymentioning
confidence: 99%
“…Six of the twenty-three shifts proclaimed in the Egyptian Education Strategic Blueprint from 2019 to 2030 concentrate on technology-enhanced renewal in making the educational process more attainable and supporting lifelong continuous learning [1,3,5]. One of the basic and substantial strategies for these transformations is via promoting universities to reinforce Massive Open Online Courses, usually abbreviated as MOOCs.…”
Section: Introductionmentioning
confidence: 99%